Synergistic Ground and Orbital Observations of Iron Oxides on Mt. Sharp and Vera Rubin Ridge. Issue 9 (23rd September 2020) - Fraeman, A. A.; Johnson, J. R.; Arvidson, R. E.; Rice, M. S.; Wellington, D. F.; Morris, R. V.; Fox, V. K.; Horgan, B. H. N.; Jacob, S. R.; Salvatore, M. R.; Sun, V. Z.; Pinet, P.; et al.
Abstract: Visible/short‐wave infrared spectral data from the Compact Reconnaissance Imaging Spectrometer for Mars (CRISM) show absorptions attributed to hematite at Vera Rubin ridge (VRR), a topographic feature on northwest Mt. Sharp. The goals of this study are to determine why absorptions caused by ferric iron are strongly visible from orbit at VRR and to improve interpretation of CRISM data throughout lower Mt. Sharp. These goals are achieved by analyzing coordinated CRISM and in situ spectral data along the Curiosity Mars rover's traverse. VRR bedrock within areas that have the deepest ferric absorptions in CRISM data also has the deepest ferric absorptions measured in situ. This suggests strong ferric absorptions are visible from orbit at VRR because of the unique spectral properties of VRR bedrock. Dust and mixing with basaltic sand additionally inhibit the ability to measure ferric absorptions in bedrock stratigraphically below VRR from orbit. There are two implications of these findings: (1) Ferric absorptions in CRISM data initially dismissed as noise could be real, and ferric phases are more widespread in lower Mt. Sharp than previously reported. (2) Patches with the deepest ferric absorptions in CRISM data are, like VRR, reflective of deeper absorptions in the bedrock. One model to explain this spectral variability is late‐stage diagenetic fluids that changed the grain size of ferric phases, deepening absorptions. Curiosity's experience highlights the strengths of using CRISM data for spectral absorptions and associated mineral detections and the caveats in using these data for geologic interpretations and strategic path planning tools. Plain Language Summary: Satellites orbiting Mars map the composition of the planet's surface, tell us about past environments, and guide rovers to interesting locations on the surface. The Curiosity rover investigated a ridge named Vera Rubin ridge where indications of the mineral hematite (Fe2 O3 ) was suggested from orbital data. In this paper, we investigate why the hematite detection on the ridge was so clear from orbit and what the implications are for how the hematite formed. We found several factors influence the orbital data, but the biggest reason hematite at Vera Rubin ridge was so easily detected from orbit was because the bedrock there was unique. Water had interacted with rocks at the ridge sometime after they were deposited, and this interaction affected the properties of the hematite and made it more visible from orbit. Curiosity's data help us reinterpret the orbital data over Mt. Sharp and reveal hematite is probably present in most of the bedrock there. Furthermore, there are other areas with particularly clear hematite detections that likely formed in a similar manner as Vera Rubin ridge. We end this paper with a discussion of lessons learned from this experience for using orbital data to guide rovers in the future. Key Points: Areas on Vera Rubin ridge with deep ferric absorptions from orbit also have deep ferric absorptions in Curiosity spectral data sets Ferric phases are more widespread on Mt. Sharp than originally reported. Diagenesis deepened ferric absorptions in several locations Combining orbital and in situ observations enhances planetary exploration